The administrative failure of the sanctioning process - Villalobos Villalobos, Vicente Brayan (2023)
In this paper, the author develops some elementary topics on the administrative lapse of the sanctioning procedure, such as the notion of sanctioning power, its constitutional basis, and its purpose and functioning, based on the regulation contained in the General Administrative Procedure Act. Finally, in order to illustrate the functioning of this institution, it presents a case decided by the Tribunal de Fiscalización Ambiental del Organismo de Evaluación y Fiscalización Ambiental, in which it declared null and void a decision of the investigating body ordering the extension of the limitation period without adequate justification.